Immersive virtual environments as a tool for exploring perceptional space. (18th December 2017) - Holth, James; Schnabel, Marc Aurel
Abstract: Digital methodologies evolve as quickly as the technologies that sustain them. Virtual reality (VR) environments are experiencing a shift from technology still in development, to a fully-fledged digital instrument with VR consumer products accessible to and usable by the general public. This paper explores the parallelism of architecture and psychology by assessing their combined impact on a user's perception of spatial qualities in an Immersive Virtual Environment (IVE). A framework for assessing the effects of densified office space is proposed. This paper concludes with a discussion on the impact of IVEs on human perception, and how this will help architectural and non-architectural disciplines gain an understanding of 'perceptional space'. Abstract : Screenshot of a low density (top), medium density (middle) and high density (bottom) node count.